Epigenetic Regulation of Survivin by Bmi1 Is Cell Type Specific During Corticogenesis and in Gliomas123. (19th December 2012) - Acquati, Serena; Greco, Azzura; Licastro, Danilo; Bhagat, Heeta; Ceric, Dario; Rossini, Zefferino; Grieve, Joan; Shaked‐Rabi, Maya; Henriquez, Nick V.; Brandner, Sebastian; Stupka, Elia; Marino, Silvia
Abstract Polycomb group proteins are essential regulators of stem cell function during embryonic development and in adult tissue homeostasis. Bmi1, a key component of the Polycomb Repressive Complex 1, is highly expressed in undifferentiated neural stem cells (NSC) as well as in several human cancers including high‐grade gliomas—highly aggressive brain tumors. Using a conditional gene activation approach in mice, we show that overexpression of Bmi1 induces repressive epigenetic regulation of the promoter of Survivin, a well‐characterized antiapoptotic protein. This phenomenon is cell type‐specific and it leads to apoptotic death of progenitor cells exclusively upon commitment toward a neuronal fate. Moreover, we show that this is triggered by increased oxidative stress‐induced DNA damage. In contrast, undifferentiated NSC as well as glioma‐initiating cells display an open chromatin configuration at the Survivin promoter and do not undergo apoptotic death. These findings raise the possibility that normal and neoplastic stem cells depend on the same mechanism for surviving the hyperproliferative state induced by increased Bmi1 expression. STEM Cells2013;31:190–202